2019
DOI: 10.3847/1538-4357/ab06fd
|View full text |Cite
|
Sign up to set email alerts
|

Global Simulations of Protoplanetary Disk Outflows with Coupled Non-ideal Magnetohydrodynamics and Consistent Thermochemistry

Abstract: Magnetized winds may be important in dispersing protoplanetary disks and influencing planet formation. We carry out global full magnetohydrodynamic simulations in axisymmetry, coupled with ray-tracing radiative transfer, consistent thermochemistry, and non-ideal MHD diffusivities. Magnetized models lacking EUV photons (hν > 13.6 eV) feature warm molecular outflows that have typical poloidal speeds 4 km s −1 . When the magnetization is sufficient to drive accretion rates ∼ 10 −8 M yr −1 , the wind mass-loss rat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
93
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 111 publications
(99 citation statements)
references
References 70 publications
3
93
1
Order By: Relevance
“…Recently Wang et al (2019) have performed the global radiation magnetohydrodynamic simulations for the first time.…”
Section: Interplay Between Photoevaporative and Mhd Windsmentioning
confidence: 99%
“…Recently Wang et al (2019) have performed the global radiation magnetohydrodynamic simulations for the first time.…”
Section: Interplay Between Photoevaporative and Mhd Windsmentioning
confidence: 99%
“…They reported that by applying an increasingly strong magnetic field on a purely thermal disk wind, a transition from magnetic pressure driven to magneto-centrifugally driven winds is to be expected. Very recently, Wang et al (2019) introduced a consistent thermochemical model to the framework of Bai (2017). In contrast to the simulations performed here, no wide plasma parameter sweep was conducted.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned earlier, we aim to conduct relatively clean numerical experiments, hence our disk model is 1 The VSI primarily occurs in the disk where gas is molecular with γ = 7/5. By a transition above the disk surface, the gas is mainly atomic in the wind zone where γ = 5/3 (e.g., Wang et al 2019). The exact value of γ affects the critical thermal relaxation timescale to trigger the VSI (Lin & Youdin 2015).…”
Section: Disk Model and Initial Conditionsmentioning
confidence: 99%
“…Global non-ideal MHD simualtions coupled with thermochemistry performed on disk winds indicate a τ ∼ 5 in the atmosphere(Wang et al 2019). More realistic thermodynamic prescription can be applied to the wind zone in the future work.…”
mentioning
confidence: 99%